2016
DOI: 10.7863/ultra.16.03107
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Ultrasound in Liver Cirrhosis: Correlation of Hepatic Artery and Portal Vein Measurements With Model for End-Stage Liver Disease Score

Abstract: We found a statistically significant correlation with elevated HAv and increasing MELD scores, splenomegaly, and presence of ascites in patients with cirrhotic liver disease; this may be a useful imaging biomarker in the evaluation of patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…Likewise, other series and our data showed that alcoholic hepatitis and severe end-stage liver disease may also cause elevated HAV. 7,8 However, our study did show that many hospitalized patients with HAV > 200 cm/s did not have a primary diagnosis of hepatobiliary disease. However, we found that all groups had elevated liver enzymes.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Likewise, other series and our data showed that alcoholic hepatitis and severe end-stage liver disease may also cause elevated HAV. 7,8 However, our study did show that many hospitalized patients with HAV > 200 cm/s did not have a primary diagnosis of hepatobiliary disease. However, we found that all groups had elevated liver enzymes.…”
Section: Discussionmentioning
confidence: 51%
“…However, a more recent publication about cirrhotic patients with endstage liver disease, using a threshold of 120 cm/s, showed a sensitivity of 42% and a specificity of 90% in predicting a MELD score > 19. 8 Tse et al 9 showed that HAV greater than 100 cm/s was 79% sensitive (Figure 1c). Like Loehfelm et al, 5 we demonstrated that elevated HAV occurs in the setting of acute cholecystitis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is noteworthy that a recently published study indicated that elevated hepatic arterial velocity is positively correlated with increasing a model for end-stage liver disease and can be used as a useful biomarker for evaluating cirrhotic patients. [ 21 ] In addition, in cirrhotic children due to biliary atresia, RI is correlated with the degree of liver cirrhosis. [ 22 ] The known etiologies of cirrhosis in children include biliary atresia, choledochal cyst, primary sclerosing cholangitis, autoimmune hepatitis, alpha1-antitrypsin deficiency, galactosemia, Wilson's disease, cystic fibrosis, Alagille syndrome, and hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used metric to determine prognosis for patients with cirrhosis is the MELDNa score. (2) However, at a given MELDNa score, the clinical manifestations of patients with end-stage liver disease are highly heterogeneous. (3) As such, a novel tool is needed to objectively capture this risk.…”
mentioning
confidence: 99%